Assessment of Health-Seeking Behavior on Maternal and Child Health among Nursing Mothers in Public Primary Health Care Centres in Kwara State, Nigeria (Federal University Gusau Faculty of Education Journal, 2026)
This study assessed the health-seeking behaviours of nursing mothers in Kwara State, Nigeria. To achieve this purpose, the cross-sectional research design was used. The population was 942,441 nursing mothers in Kwara state, with a target population of 46,423 nursing mothers attending postnatal clinics in Public Primary Health Centres in Kwara State, Nigeria. The sample size of 420 was selected using multistage sampling procedures of stratified, proportionate, simple random and convenience. The instrument for data collection was a structured questionnaire developed by the researcher. Descriptive statistics of frequency and simple percentages were used to describe the demographic characteristics of the respondents. The research question was answered using mean and standard deviation, while the inferential statistic of a one-sample t-test was used to test the stated hypothesis at a 0.05 level of significance. The result revealed that the health-seeking behaviour of nursing mothers in Kwara State is significant (t = 136.490; p = 0.000). Based on the results, the study concluded that nursing mothers in Kwara State have good health-seeking behaviour. Based on the conclusion, the study recommends, among others, the need for increased awareness and health education campaigns to disseminate reliable and accurate information on health-seeking behaviour to nursing mothers to maintain the already established good health-seeking behaviour.